Analisis Rasio Keuangan Daerah untuk Menilai Kinerja Keuangan Pemerintah Daerah Kepulauan Meranti - Novira Sartika (Inovbiz: Jurnal Inovasi Bisnis, 2019)
This study aims to determine the financial performance of the Kepulauan Meranti Regency Government for the 2012-2016 fiscal year measured by financial ratio analysis. This research method is quantitative descriptive. The data are secondary data in the form of Budget Realization Report (LRA) for the 2012-2016 fiscal year. The analysis shows that the financial performance of the Kepulauan Meranti Regency Government measured by ratio of regional financial efficiency shows efficient with an average ratio of 72,84%. Then when measured by ratio of regional financial independence shows very low with an average ratio of 3,45%. Furthermore, if measured by ratio of the effectiveness of Own-Source Revenue (PAD) shows effective with an average ratio of 103,65%. When observed by degree of decentralization ratio shows average ratio 3,31%. The Last, measured from the equivalent ratio, especially the ratio of operating expenditure shows average ratio 74,14% and capital expenditure 21,80%. We conclude that the financial performance of the Kepulauan Meranti Regency Government is has been quite efficient in managing its finances because it has been able to reduce the amount of regional expenditure that does not exceed regional income. This is seen from the average ratio of regional financial efficiency of 72.84%. In addition, the Regional Government has been effective in managing PAD. This is evident from the average PAD effectiveness ratio of 103.65%. This shows that the acceptance of PAD has been said to be quite good and in accordance with the targeted.